2021
DOI: 10.3390/membranes11010051
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Degradation of PSF-PUR Blend Hollow Fiber Membranes—Assessment of Changes in Properties and Morphology after Hydrolysis

Abstract: In this study, we focused on obtaining polysulfone-polyurethane (PSF-PUR) blend partly degradable hollow fiber membranes (HFMs) with different compositions while maintaining a constant PSF:PUR = 8:2 weight ratio. It was carried out through hydrolysis, and evaluation of the properties and morphology before and after the hydrolysis process while maintaining a constant cut-off. The obtained membranes were examined for changes in ultrafiltration coefficient (UFC), retention, weight loss, morphology assessment usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The PSF-PUR-2 membrane, with the highest increase, contained 30% by weight of PUR, PSF-PUR-1 and PSF-PUR-4 membranes, for which similar increases were recorded (UFC changes were recorded as being between the highest and the lowest ratio UFC NaOCl UFC 0 contained 20 wt.% PUR, while the PSF-PUR-3 membrane contained only 10 wt.% PUR. Comparing the UFC with the literature data, the expected results were obtained, confirming that the degradation of membranes (hydrolysis or biodegradation) caused an increase in the UFC value [29,30,33,35,39,41].…”
Section: Ultrafiltration Coefficientsupporting
confidence: 74%
“…The PSF-PUR-2 membrane, with the highest increase, contained 30% by weight of PUR, PSF-PUR-1 and PSF-PUR-4 membranes, for which similar increases were recorded (UFC changes were recorded as being between the highest and the lowest ratio UFC NaOCl UFC 0 contained 20 wt.% PUR, while the PSF-PUR-3 membrane contained only 10 wt.% PUR. Comparing the UFC with the literature data, the expected results were obtained, confirming that the degradation of membranes (hydrolysis or biodegradation) caused an increase in the UFC value [29,30,33,35,39,41].…”
Section: Ultrafiltration Coefficientsupporting
confidence: 74%
“…PECUUs obtained in the CCTP can be also utilized as components in blends with polysulfone, producing partly degradable hollow-fiber membranes [38][39][40]. The conducted tests clearly showed that parts of the membranes related to PECUUs are partially degraded while maintaining a constant membrane cut-off point.…”
Section: Poly(urea-urethane)s Derived From Oligo(ester-carbonate) Dio...mentioning
confidence: 92%
“…The preparation route of polymer blends starts with the selection of a proper parent polymer with desired physical and chemical properties to complement another polymer. The composition of polymer blends requires proper adjustment to form a miscible blend with desired characteristics, followed by the spinning of the polymer dope with phase inversion [ 174 , 175 , 176 , 177 , 178 ].…”
Section: Types Of Hollow Fiber and Their Preparation Routementioning
confidence: 99%